Loss of Setd2 promotes Kras-induced acinar-to-ductal metaplasia and epithelia–mesenchymal transition during pancreatic carcinogenesis. Issue 4 (11th July 2019) - Niu, Ningning; Lu, Ping; Yang, Yanlin; He, Ruizhe; Zhang, Li; Shi, Juanjuan; Wu, Jinghua; Yang, Minwei; Zhang, Zhi-Gang; Wang, Li-Wei; Gao, Wei-Qiang; Habtezion, Aida; et al.
Abstract : Objective: SETD2, the sole histone H3K36 trimethyltransferase, is frequently mutated or deleted in human cancer, including pancreatic ductal adenocarcinoma (PDAC). However, whether SETD2/H3K36me3 alteration results in PDAC remains largely unknown. Design: TCGA(PAAD) public database and PDAC tissue array with SETD2/H3K36me3 staining were used to investigate the clinical relevance of SETD2 in PDAC. Furthermore, to define the role of SETD2 in the carcinogenesis of PDAC, we crossed conditional Setd2 knockout mice ( Pdx cre Setd2 flox/flox ) together with Kras G12D mice. Moreover, to examine the role of SETD2 after ductal metaplasia, Crisp/cas9 was used to deplete Setd2 in PDAC cells. RNA-seq and H3K36me3 ChIP-seq were performed to uncover the mechanism. Results: SETD2 mutant/low expression was correlated with poor prognosis in patients with PDAC. Next, we found that Setd2 acted as a putative tumour suppressor in Kras-driven pancreatic carcinogenesis. Mechanistically, Setd2 loss in acinar cells facilitated Kras-induced acinar-to-ductal reprogramming, mainly through epigenetic dysregulation of Fbxw7 . Moreover, Setd2 ablation in pancreatic cancer cells enhanced epithelia–mesenchymal transition (EMT) through impaired epigenetic regulation of Ctnna1 . In addition, Setd2 deficiency led to sustained Akt activation via inherent extracellular matrix (ECM) production, which would favour their metastasis. Conclusion: Together, our findings highlight the function of SETD2 during pancreatic carcinogenesis, which would advance our understanding of epigenetic dysregulation in PDAC. Moreover, it may also pave the way for development of targeted, patients-tailored therapies for PDAC patients with SETD2 deficiency.